Parametric Modeling of Flat Rod Structures - Stefańska, Anna; Rokicki, Wieslaw (IOP conference series. Materials Science and Engineering, 2020)
Thanks to the use of advanced digital tools and the achievements of knowledge encompassing numerous fields of science including mathematics, computer science, and even genetics, architects now have the means to create multi-variant design solutions. The quantifiable benefits of interdisciplinary design are increasingly recognized within the field of architecture. As a result, a surprising variety of new ideas and designs emerge. These are often the result of advanced material and structural optimization, and their technological qualities become as important as their visual reception. The subject of this research paper is presenting the results of modeling various configurations of flat rod trusses. The aim of the analysis was comparing the efficiency of the use of materials in differently configured trusses, including trusses created via parametric modeling.